Misplaced drainage tube inserted in the vein in a percutaneous nephrostomy: a case series. Issue 9 (September 2022) - Song, Yuanming; Zhao, Changyong; Zhang, Zhongyi; Zhan, Shun; Qiu, Zuze; Li, Daobing
Percutaneous nephrostomy is a critical procedure for establishing surgical pathways from the skin to the renal collecting system. The drainage tube involved in the procedure rarely deviates into the renal vein. Herein, we report three cases in which the related drainage tube was mistakenly inserted into the renal vein and inferior vena cava after the renal vein was injured during percutaneous nephrostomy. In the three cases, the nephrostomy tube and double-J tube were gradually withdrawn from the renal pelvis or renal calyces under computed tomography (CT) monitoring. In case 1, the fistula tube was not completely withdrawn in time into the renal, causing multiple thromboses in the vein. The fistula was successfully withdrawn from the vena cava after the filter was placed. Finally, the stones were cleared in two cases and one case was discharged without complications after substantial renal function recovery. A safe and reliable approach is to gradually withdraw, within a short timeframe and under CT monitoring, an ectopic renal vein or inferior vena cava drainage tube into the renal pelvis. Removal of the catheter to the renal pelvis or calyces within 3 days can reduce thrombotic complications.